The culture for the recognition of the identity: case of the fang culture of Equatorial Guinea - Obiang-Mikue , Bonifacio Nguema (2023)
Culture is a manifestation that helps the recognition and identification of a certain social group or individual. It is defined as the set of manifestations that express the way of thinking, way of living, customs and intelligence developed by a social group. This paper clearly deals with culture in the Fang ethnic group of Equatorial Guinea. Therefore, the purpose of this research is to make known that culture is an essential and vital element for the Fang man, currently a lively collapse is being observed. As this research deals with a socio-cultural issue such as the Fang culture, it was necessary to adopt a qualitative methodology. The reasons that induced to apply this approach is because there are studies on social relations. One of the most relevant results is that all respondents believe that culture has an influence on the person. It must be said that in the current context, it is not possible to speak of a culture apart from a social group. And as the most revealing conclusion, there is the issue of the decline of the fang culture. It is noted that there are several reasons that are fueling this decline. Globalization and/or modernism are pointed out as causes.